Using infrared thermography to assess emotional responses to infants - Esposito, Gianluca (2017)
Adult–infant interactions operate simultaneously across multiple domains and at multiple levels – from physiology to behaviour. Unpackaging and understanding them, therefore, involve analysis of multiple data streams. In this study, we tested physiological responses and cognitive preferences for infant and adult faces in adult females and males. Infrared thermography was used to assess facial temperature changes as a measure of emotional valence, and we used a behavioural rating system to assess adults' expressed preferences. We found greater physiological activation in response to infant stimuli in females than males. As for cognitive preferences, we found greater responses to adult stimuli than to infant stimuli, both in males and females. The results are discussed in light of the Life History Theory. Finally, we discuss the importance of integrating the two data streams on our conclusions.